2018
DOI: 10.1021/acs.langmuir.8b00795
|View full text |Cite
|
Sign up to set email alerts
|

Doubly pH Responsive Emulsions by Exploiting Aggregation of Oppositely Charged Nanoparticles and Polyelectrolytes

Abstract: We present a simple and modular approach to realize highly stable pH responsive Pickering emulsion from mixtures of commercially available oppositely charged nanoparticle and polyelectrolyte. While highly charged nanoparticles and polyelectrolytes when used solely do not stabilize emulsions, we show that the electrostatic attraction between oppositely charged nanoparticles and polyelectrolytes can be exploited to formulate emulsions with long-term stability of up to 8 months. The Ludox CL nanoparticles and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…For example, in fuel production, oil transfer, and emulsion polymerization, the emulsion requires only temporary stabilization and subsequent demulsification. Therefore, the Pickering emulsions responding to various stimuli have received considerable attention in recent years. Various triggers such as light irradiation, , pH, CO 2 , temperature, magnetic field, , and specific ion concentration have been reported. Among these triggers, CO 2 is widely studied because of its low cost, environment friendly, and easily removed from the system .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in fuel production, oil transfer, and emulsion polymerization, the emulsion requires only temporary stabilization and subsequent demulsification. Therefore, the Pickering emulsions responding to various stimuli have received considerable attention in recent years. Various triggers such as light irradiation, , pH, CO 2 , temperature, magnetic field, , and specific ion concentration have been reported. Among these triggers, CO 2 is widely studied because of its low cost, environment friendly, and easily removed from the system .…”
Section: Introductionmentioning
confidence: 99%
“…The emulsions formed in this composition range exhibit extraordinary stability of more than 12 months. The weakly charged or charge neutral heteroaggregates in the binary mixtures formed due to attractive electrostatic interaction readily adsorbed around the drop surface created during homogenization, thus forming stable Pickering emulsions. , The concentration of the surface-active heteroaggregates determines the final diameter of the emulsion drops formed because of arrested coalescence . In the intermediate composition (from Φ a = 0.2 to Φ a = 0.8), the diameters of the emulsion drops are in a narrow size ranging from 50 to 70 μm.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In such emulsion systems, the stability and size distribution of the emulsion droplets strongly depend on the microstructure and the dimensions of the heteroaggregates, which is a function of parameters such as the charge ratio, number ratio, size ratio, concentration, and the contact angles of the particles. 37,38 An understanding and optimization of the conditions to achieve controlled heteroaggregation are essential for the preparation of processable Pickering emulsion for the fabrication of porous ceramic structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of Pickering emulsions stabilized by Pickering emulsifiers based on electrostatic interactions is expected to be easily controlled by outside triggers, such as pH or CO 2 . For example, Shahid et al 56 reported a Pickering emulsion stabilized by the product of electrostatic binding between positively charged nanoparticles (SiO 2 @Al 2 O 3 ) and negatively charged polyelectrolytes (poly(4-styrenesulfonate) sodium salt), and the prepared Pickering emulsion was pH-responsive. Therefore, we speculate that the stability of the Pickering emulsion prepared from the electrostatic binding product of CNCs-M2005 is also pH-responsive.…”
Section: ■ Results and Discussionmentioning
confidence: 99%